Internationalising a learning environment instrument for evaluating transnational online university courses. - Yeo, Shelley; Taylor, Peter; Kulski, Martijntje (Kluwer Academic Publishers, 2006)
This article describes the adaptation and validation of the Constructivist OnLine Learning Environment Survey (COLLES) for use in the transnational higher education context. As higher education becomes a more global phenomenon, ‘borderless’ education, either online or by distance education, is becoming a reality and there is a need for remote evaluation of course delivery and student learning. Curtin University of Technology is managing supported online delivery of Business Studies Degree and Diploma courses to four partner institutions of the African Virtual University, an initiative based in Nairobi, Kenya. Evaluation of students’ learning has included an online survey about the provision of resources and the quality of the learning environment in the various computer-based classrooms. Embedded in this instrument has been the adapted COLLES, providing a concomitant opportunity to test the properties and usefulness of the learning environment instrument. Problematic issues surrounding adaptation of the instrument have included the consequences of modifying the wording and establishing or confirming the meaning of the latent constructs in partially online courses and for transnational students. The process of establishing the validity and reliability of the scales is discussed.